Peran ROE Terhadap Pengaruh DER Dan Firm Size Pada Tobin’s Q Sub Sektor Kabel Yang Terdaftar Di BEI - Nelly Ervina; Yerisma Welly; Ernest Grace (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
This study aims to look at the effect of firm size and DER on Tobin's Q and ROE's ability to moderate the relationship of firm size and DER with Tobin's Q in the cable sub-sectors listed on the Indonesia Stock Exchange in the 2014-2018 period. The research sample is cable sub-sector companies listed on the Stock Exchange in the 2014-2018 period. Data analysis techniques using multiple regression tests, moderation regression tests, hypothesis testing (f test and t test) and MRA test. The results of this study indicate the test of multiple linear regression that is confirm size and DER has a positive effect on Tobin's Q. Moderated regression test with interaction test that is ROE strengthens firm-sized and DER relationships with Tobin's Q. Test R and R2 namely there is a strong relationship between firm size and DER variables with Tobin's Q variable Tests that firm size and DER have a significant effect on Tobin's Q. The second hypothesis test, ROE is able to moderate but not significantly relationship firm size and DER with Tobin's Q